2020
DOI: 10.1176/appi.ajp.2020.19091000
|View full text |Cite
|
Sign up to set email alerts
|

20-Year Trends in the Pharmacologic Treatment of Bipolar Disorder by Psychiatrists in Outpatient Care Settings

Abstract: Pharmacological options for treating bipolar disorder have increased over the past 20 years, with several second-generation antipsychotics receiving regulatory approval in the 1990s. The authors describe trends in use of pharmacological agents in the outpatient management of bipolar disorder.Methods: Using nationally representative data from the 1997-2016 National Ambulatory Medical Care Surveys, the authors examined trends in the use of mood stabilizers, firstand second-generation antipsychotics, and antidepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
150
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 156 publications
(171 citation statements)
references
References 46 publications
12
150
0
9
Order By: Relevance
“…It also revealed that the prescription rate of lithium carbonate, which is the first-choice drug for bipolar disorder [ 11 ], is only approximately 20% and is decreasing each year [ 11 ]. This trend was also consistent with the longitudinal data analysis results obtained from the National Ambulatory Medical Care Surveys [ 12 ]. In a study using Swedish national registries, 70% of patients with bipolar disorder were prescribed antidepressants [ 13 ].…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…It also revealed that the prescription rate of lithium carbonate, which is the first-choice drug for bipolar disorder [ 11 ], is only approximately 20% and is decreasing each year [ 11 ]. This trend was also consistent with the longitudinal data analysis results obtained from the National Ambulatory Medical Care Surveys [ 12 ]. In a study using Swedish national registries, 70% of patients with bipolar disorder were prescribed antidepressants [ 13 ].…”
Section: Introductionsupporting
confidence: 90%
“…In a study using Swedish national registries, 70% of patients with bipolar disorder were prescribed antidepressants [ 13 ]. In the United States, antidepressants are prescribed to 57.5% of patients with bipolar disorder [ 12 ]. In a study of nationwide and population-based prescription patterns in the Danish population, 59.12% of patients with bipolar disorder were prescribed antidepressants [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological treatment of bipolar disorder has changed over the last several decades. Two major changes were a large increase in prescriptions of atypical antipsychotics [1][2][3][4][5][6] and routine prescribing of 2 or more psychiatric drugs, or polypharmacy [3,5,[7][8][9]. The increase in prescriptions of atypical antipsychotics occurred in parallel with a decline in prescriptions of lithium [2,10,11], the traditional gold standard for maintenance treatment for bipolar disorder [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the undeniable evidence in favour of its application in BD, a descendent tendency in the use of lithium has been noticed in the US (Rhee et al, 2020) and in numerous European countries (Bohlken et al ., 2020;Karanti et al, 2016;Kessing et al, 2016;Lyall et al, 2019). In several of them it has changed from being the most prescribed drug to the least one, even behind the controversial antidepressants.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, over the last two decades, the decrease in lithium´s use is not widespread and in certain countries the lithium´s prescription rate has remained high. In some countries, more than 50% of bipolar patients are treated with lithium while in the US for example, only the 17% (Kessing et al, 2019;Parabiaghi et al, 2015;Renes et al, 2018, Rhee et al, 2020 (Table 1).…”
Section: Introductionmentioning
confidence: 99%